Regional patterns in the incidence of aplastic anemia in Thailand - Surapol Issaragrisil (2018)
The annual incidence of aplastic anemia has been determined in a rigorous and standardized epidemiologic study conducted in Thailand. A total of 374 cases were identified over a period of 3-6 years in three geographically defined and distinct regions of the country; Bangkok, Khonkaen in the northeast, and Songkla in the south. The incidence was 3.9 cases per million persons in Bangkok, 3.0 per million in Songkla, and 5.0 per million in Khonkaen. These rates are as high or higher than in any region of Europe or Israel as reported in the International Agranulocytosis and Aplastic Anemia Study, in which the methods and case definition were the same. Rates were stable over the course of the study. There were marked differences in incidence between northern and southern rural regions of Thailand, and among Bangkok suburbs. These differences, together with an unusual peak in the incidence among young people in Bangkok, suggest the possibility of occupational and environmental factors in the etiology of aplastic anemia.